2019
DOI: 10.1002/xrs.3033
|View full text |Cite
|
Sign up to set email alerts
|

Light element depth distribution by the intensity ratio of incoherent and coherent scattering

Abstract: A method is proposed for analyzing the distribution of elements with a small atomic number Z < 9 over the depth of the substrate. The method is based on measuring the ratio of incoherent and coherent scattering peaks intensities at different exit angles of X‐rays from the sample surface. Varying the beam exit angle at a constant scattering angle makes it possible to vary the depth of radiation penetration into the sample by almost two orders of magnitude and, correspondingly, to vary the information averaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The uniqueness of this method lies in the fact that it is suitable for the rapid identification of elements with a small atomic number down to hydrogen ( Z = 1) with tables . Recently, the ratio of Compton and Rayleigh scattering intensities has been used in solving both fundamental problems of determining the effective atomic number and mass absorption coefficients and applied problems of adjusting the composition in the XRF analysis, and also for determining the fraction of light elements in the sample bulk and the distribution of light elements along its depth . In our previous work, it was shown that the trueICIR dependence on the atomic number can be used as a calibration function for identification of single‐component and binary materials in certain ranges of effective atomic numbers Zeff .…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of this method lies in the fact that it is suitable for the rapid identification of elements with a small atomic number down to hydrogen ( Z = 1) with tables . Recently, the ratio of Compton and Rayleigh scattering intensities has been used in solving both fundamental problems of determining the effective atomic number and mass absorption coefficients and applied problems of adjusting the composition in the XRF analysis, and also for determining the fraction of light elements in the sample bulk and the distribution of light elements along its depth . In our previous work, it was shown that the trueICIR dependence on the atomic number can be used as a calibration function for identification of single‐component and binary materials in certain ranges of effective atomic numbers Zeff .…”
Section: Introductionmentioning
confidence: 99%